Customer relationship management architecture in the pharmaceutical industry. (11th May 2004) - Alt, Rainer; Oesterle, Hubert; Puschmann, Thomas; Barak, Vladimir; , Thomas Huber
The pharmaceutical industry is undergoing a fundamental transformation. Institutional regulations that have been in place for decades are being removed and competitive pressures on various levels force pharmaceutical companies to adopt customer-oriented strategies. Information technology is an important enabler to improve the interaction with key customer segments, such as physicians, and patients. This research presents a framework that has been elaborated in cooperation with nine companies and applied at a major pharmaceutical company for the development of process portals. These portals include services that support the processes of specific customer segments from internal and external sources. The architecture shows the implications of process portals on a strategic, a process and a systems level.